2023
DOI: 10.1101/2023.05.31.543061
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ribosome clustering and surface layer reorganization in the microsporidian host-invasion apparatus

Abstract: During host cell invasion, microsporidian spores translocate their entire cytoplasmic content through a thin, hollow superstructure known as the polar tube. To achieve this, the polar tube transitions from a compact spring-like state inside the environmental spore to a long needle-like tube capable of long-range sporoplasm delivery. The unique mechanical properties of the building blocks of the polar tube allow for an explosive transition from compact to extended state and support the rapid cargo translocation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…We also showed that PTP4-6 are members of the RBL family, which may contain additional, yet uncharacterized proteins that form part of the unique microsporidian infection apparatus. A recent study identified multiple RBL proteins as interaction partners of V. necatrix PTP3 ( 80 ), one of the main components of the polar tube ( 81 ). Our findings of the close relationship between PTP4-6 and RBL proteins, and the interaction of various RBL proteins with the microsporidian polar tube indicate an important role of RBLs in microsporidian host-invasion and incentivize further experimental research on this enriched protein family in Nosematida.…”
Section: Resultsmentioning
confidence: 99%
“…We also showed that PTP4-6 are members of the RBL family, which may contain additional, yet uncharacterized proteins that form part of the unique microsporidian infection apparatus. A recent study identified multiple RBL proteins as interaction partners of V. necatrix PTP3 ( 80 ), one of the main components of the polar tube ( 81 ). Our findings of the close relationship between PTP4-6 and RBL proteins, and the interaction of various RBL proteins with the microsporidian polar tube indicate an important role of RBLs in microsporidian host-invasion and incentivize further experimental research on this enriched protein family in Nosematida.…”
Section: Resultsmentioning
confidence: 99%